"Under the Same Quilt": The Paradoxes of Sex Between Men in the Cultural Revolution. Issue 1 (2nd January 2017) - Worth, Heather; Jing, Jing; McMillan, Karen; Su, Chunyan; Fu, Xiaoxing; Yuping, Zhang; Zhao, Rui; Cui, Jia; Kelly-Hanku, Angela; Youchun, Zhang
ABSTRACT: This article describes the paradoxes experienced by homosexual men during the Chinese Cultural Revolution. Interviews with 31 elderly Chinese gay men were carried out in four cities in China in 2011. Although homosexual men were terribly persecuted, chaotic situations and dislocations of youth from their families provided young homosexual men with a remarkable degree of personal freedom and the opportunity to explore same-sex relations. Analysis of this seemingly contradictory conflation of persecution and freedom will allow us to explore the conditions and effects of the coming of age of homosexual men in a unique epoch in Chinese history.